公式
admin
撰写于 2022年 11月 06 日

$\sum_{i=0}^n i^2 = \frac{(n^2 + n)(2n+1)}{6}$
$\sum_{i=0}^n i^2 = \frac{(n^2 + n)(2n+1)}{6}$
$\sum_{i=0}^n i^2 = \frac{(n^2 + n)(2n+1)}{6}$
$\sum_{i=0}^n i^2 = \frac{(n^2 + n)(2n+1)}{6}$
$\sum_{i=0}^n i^2 = \frac{(n^2 + n)(2n+1)}{6}$

公式

$\sum_{i=0}^n i^2 = \frac{(n^2 + n)(2n+1)}{6}$
$\sum_{i=0}^n i^2 = \frac{(n^2 + n)(2n+1)}{6}$
$\sum_{i=0}^n i^2 = \frac{(n^2 + n)(2n+1)}{6}$
$\sum_{i=0}^n i^2 = \frac{(n^2 + n)(2n+1)}{6}$
$\sum_{i=0}^n i^2 = \frac{(n^2 + n)(2n+1)}{6}$

上一篇
流程图
下一篇
233

猜您想看

评论区(暂无评论)

这里空空如也,快来评论吧~

我要评论